Celebração do êxito e naturalização da precariedade do trabalho docente na educação básica : crítica a racionalidade neoliberal no Prêmio Educador Nota 10 - Estormovski, Renata Cecilia (2021)
The way in which education is constituted nowadays is closely related to the neoliberal rationality which, as part of its prescriptions, strengthens strategies that bring schools closer to the desires of capital and make teaching work a precarious activity. As discussed throughout this dissertation, teacher awards are included among these initiatives, establishing a particular perspective on success in teaching that, while celebrating the success of a portion of the teachers, naturalizes the limitations imposed on the work of category. In order to develop this hypothesis, a qualitative and documental analysis of the Prêmio Educador Nota 10 is carried out, in which two complementary methods are used: network ethnography and content analysis. Based on this study, the intention is to build an argument that clarifies the following problem: How does the definition of teacher success portrayed in the Prêmio Educador Nota 10 reinforce connotations that contribute to the naturalization of the precariousness of teaching work? To answer it, the objective of the research is to investigate how the Prêmio Educador Nota 10, through a particular definition of teaching success, collaborates with the reinforcement of conceptions that naturalize the precariousness of the teacher's work by delegating only the success of educational practices to their individual sphere of action. The dissertation is divided into three main sections (in addition to initial and final considerations). In the first, the theoretical frameworks that support the research are built, contextualizing the relations between the State, the third sector and education in neoliberal society, aiming to understand how, in this movement, the teaching work is conceived. Then, the content of the Prêmio Educador Nota 10 proposal is discussed, identifying the elements pointed out by him as guidelines for successful teaching practice and mapping the political network involved in this initiative. Finally, it is analyzed how the way in which the award recognizes the teaching experiences is related to the way in which the legislation provides for the professional valuation of the teacher and implements it, with implications that favor the precariousness of teaching work and its consequent naturalization. In the end, the hypothesis defined for the research is confirmed, clarifying that initiatives such as the award under analysis normalize the unequal conditions in which basic education teachers work, materializing divergent perspectives of professional valorization and minimizing the effects of precariousness in their work.